First Meeting of the Standing Committee of the National Development Council New Delhi, January 1955 - Planning Commission (Planning Commission, 1955)
In his opening remarks, the Chairman welcomed the formation of the Standing Committee of the National Development Council as a step which would help in considering basic questions, especially in relation to the Second Five-Year Plan. Foreign observers had remarked that India was now becoming social minded and that emphasis was shifting from the purely political to the social and economic plane There was interest as to the kind of outlook that would be developed in India in dealing with the problems of poverty and unemployment. These problems were a challenge which had to be faced and much would depend upon the turn given to the policies adopted in planning. There were a number of eminent statisticians and planners from foreign countries row working at the Indian Statistical Institute in Calcutta. It was for us to decide how far their advice would be useful, but the 'discussions with them would throw light on our problems and enable us to think further about them
National Development Council
Government of India Planning Commission
Keywords: Standing Committee; National Development Council; Planning Commission; Rashtrapati Bhavan; Summary record; First meeting; First Five Year Plan; Second Five Year Plan